Fungi : diversity and biotechnology - Deshmukh, S. K. (Sunil K.); Rai, M. K. (Jodhpur : Scientific Publishers (India), 2005)
Contributed articles
Includes bibliographical references
Keywords: Fungi -- Biotechnology; Fungi